Association of body mass index trajectory and hypertension risk: A systematic review of cohort studies and network meta-analysis of 89,094 participants - Tan, Ling; Long, Lin-zi; Ma, Xiao-chang; Yang, Wen-wen; Liao, Fei-fei; Peng, Yu-xuan; Lu, Jie-ming; Shen, A-ling; An, Dong-qing; Qu, Hua; Fu, Chang-geng (Frontiers in Cardiovascular Medicine, 2023)
Introduction Body mass index (BMI) trajectories, such as non-linear time trends and nonlinear changes in BMI with age, can provide information on the underlying temporal health patterns. The relationship between BMI trajectories and the risk of hypertension remains controversial. Methods PubMed, Embase, Cochrane, Scopus, and Web of Science databases were searched from their inception to January 31, 2022. We categorized BMI trajectories as “Stable high,” “table normal,” “Stable low,” “Fluctuated (sharp increase),” and “Fluctuated (elevated-decrease).” The main outcome was the relative risk for the prevalence of hypertension in the different BMI trajectories. Potential sources of heterogeneity were examined using meta-regression and subgroup analysis. A publication bias test and Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach were also used. Results The 18 cohort studies included 89,094 participants. Compared with the “Stable normal” trajectory, “Stable high,” “Fluctuated (sharp increase),” and “Fluctuated (elevated-decrease)” trajectories were associated with an increased relative risk of hypertension: [RR (95% CI)]: 1.80 (1.29 2.50), p < 0.001; 1.53 (1.27 1.83), p < 0.001; 1.30 (1.24 1.37), p = 0.001, respectively. The “Stable low” trajectory was associated with a reduced risk of hypertension [0.83 (0.79 0.83), p < 0.001]. The “Stable high” trajectory (surface under the cumulative ranking curve = 88.1%) had the highest probability of developing hypertension in the population. The certainty of the evidence for direct comparisons of the incidence of hypertension between various BMI trajectories was generally very low. Conclusion Our findings suggested that “Stable high,” “Fluctuated (sharp increase),” and “Fluctuated (elevated-decrease)” trajectories were associated with an increased relative risk of hypertension, with the “Stable high” trajectory most likely associated with hypertension. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=308575], identifier [CRD42022308575].